Compaction and restraining effects of insoluble sediments in underground energy storage salt caverns. (15th June 2022) - Li, Peng; Li, Yinping; Shi, Xilin; Zhao, Kai; Liang, Xiaopeng; Ma, Hongling; Yang, Chunhe; Liu, Kai
Abstract: Compared with the salt domes formed by marine deposits abroad, the salt formations in China have bedded strata of lacustrine deposition, which contain rock salts and nonsalt interlayers. During the leaching phase, rock salts will dissolve to form a cavern that is used for storing oil or natural gas, whereas the nonsalt interlayers will soften and detach from the cavern walls, accumulating to the cavern bottom. These sediments will restrain the cavern walls and increase the working capacity because of the pore space in the sediments. Therefore, the stress and porosity of the sediments are key parameters for the assessment of the compaction and restraining effects of insoluble sediments. In this work, a mechanical element model of the sediments is proposed to predict the stress and porosity of the sediments in a cylindrical salt cavern. The depth of the sediments is introduced to analyze the compaction effect. The influencing factors of the equations of stress and porosity are then discussed using different friction coefficients, lateral stress coefficients, and hydraulic radii. To investigate the restraining effect of the sediments on the stability of the salt cavern, coupled numerical simulations are carried out using the discrete-continuous coupled method. Comparing the numerical simulation results of the salt cavern with and without sediments, the porosity of the sediments decreases, and the effective stress increases with creep time. The increasing rates of deformation and shrinkage gradually decrease because of the presence of sediments, which is favorable to improving the stability of the salt cavern. The numerical simulation results of the salt cavern with different variables indicate that the shrinkage of the cavern and porosity of the sediments are not sensitive to the sediment density, ball friction, or wall friction. This study can provide a reference for predicting the stress and porosity of the sediments and for investigating the stability of salt caverns with sediments. Highlights: A mechanical model of sediments for predicting the stress and porosity is proposed. The depth of the sediments is proposed to investigate the compaction effect. A discrete continuous coupled model is established to investigate the restraining effect. The model considering the restraining effect calculates the stability of salt cavern accurately.